Effect of Ultrasonic Extraction on Production and Structural Changes of C-Phycocyanin from Marine Spirulina maxima - Woon Yong Choi (International Journal of Molecular Sciences, 2018)
This work first showed that very high amounts of phycocyanins, such as 11.3 mg/mL C-phycocyanin (C-PC), 3.1 mg/mL allophycocyanin (APC), and 0.8 mg/mL phycoerythrin (PE), can be obtained using an ultrasonic extraction process (UE) with a 60 kHz frequency and 3 h of process time at 25 °C, without any other pretreatments. These yields were higher than those from most conventional water extractions at 4 °C for 24 h (Control condition) or at 25 °C for 24 h (WE), namely, 9.8 and 5.7 mg/mL C-PC, 2.3 and 1.2 mg/mL APC, and 0.7 and 0.3 mg/mL PE, respectively. These yields were also shown to be even higher than yields from other reported data. Structural changes in C-PC in the extracts were also found for the first time, according to extraction conditions, showing that the total concentration of C-PC and of the α-subunit of C-PC in the UE were much higher than in the WE, with little difference in the amount of β-subunit of C-PC in the UE or WE. It was also shown that the structural changes in C-PC in the WE decreased both antioxidant and anti-inflammation activities—29.83% vs. 32.09% of α,α-diphenyl-β-picrylhydrazyl (DPPH) scavenging activity and 8.21 vs. 7.25 µM of NO production for the WE and UE, respectively—while the UE, with similar patterns to standard C-PC, showed very high biological effects, which may suggest that the biologically active part is the α-subunit of C-PC, not the β-subunit.